Polarization correlations between photons emitted in dielectronic recombination of high-Zions - Matula, Oliver; Fritzsche, Stephan; Surzhykov, Andrey (Physica scripta, 2013)
Polarization correlations between photons emitted in dielectronic recombination (DR) of initially hydrogen-like ions are analysed based on a density matrix approach and relativistic Dirac's theory. Special attention is given to the non-dipole contributions in the photon field expansion of the electron-photon interaction. In particular, we apply our general formalism to the radiative decay of the L1/2L3/2 resonance that is formed in DR of (initially) hydrogen-like uranium ions. The corresponding calculations show that a mixing between the leading electric dipole (E1) and the magnetic quadrupole (M2) transitions can significantly affect the polarization correlations between the emitted photons.
Gesehen am 29.06.2021